Milk Macrophage Function in Bovine Leukemia Virus-Infected Dairy Cows - Lima, Ewerton de Souza; Blagitz, Maiara Garcia; Batista, Camila Freitas; Alves, Alexandre José; Fernandes, Artur Cezar de Carvalho; Ramos Sanchez, Eduardo Milton; Frias Torres, Hugo; Diniz, Soraia Araújo; Silva, Marcos Xavier; Della Libera, Alice Maria Melville Paiva; de Souza, Fernando Nogueira (Frontiers in Veterinary Science, 2021)
The implications of bovine leukemia virus (BLV) on innate and adaptive immune responses have been widely investigated; however, the effects of BLV on mammary gland immunity require further investigation. The present study investigated the viability, phagocytic capacity and intracellular production of reactive oxygen and nitrogen species (RONS) by macrophages in milk samples from dairy cows naturally infected with BLV with or without persistent lymphocytosis (PL). No effect of BLV-infection in the overall number of macrophages per mL and in the percentage of viable macrophages among overall milk viable cells was found. Furthermore, BLV-infected dairy cows had a higher frequency of viable milk macrophages, while healthy animals had a tendency toward a higher percentage of apoptotic milk macrophages. The percentage of milk macrophages that phagocytosed Staphylococcus aureus in seronegative animals was higher than that in BLV-infected dairy cows. No effect of BLV-infection on the intracellular RONS production and the intensity of phagocytosis by milk macrophages was observed. Thus, this study provides new insights into the implications of BLV infections in the bovine mammary gland.